Mixed type total anomalous pulmonary venous connection: Early results and midterm outcomes of surgical correction. Issue 4 (10th February 2021) - Jaswal, Vivek; Thingnam, Shyam K. S.; Mishra, Anand K.; Mahajan, Sachin; Kumar, Vikas; Rohit, Manoj K.; Mandal, Banashree
Abstract: Background and Aim of the Study: The morphological heterogeneity of anomalous pulmonary venous drainage in mixed type total anomalous pulmonary venous connection (TAPVC) has important implications in preoperative diagnosis and surgical repair resulting in high mortality in these patients. Methods: A retrospective review of 14 patients with mixed type TAPVC undergoing biventricular repair between January 2012 and December 2019 was conducted. A descriptive analysis was done, highlighting the anatomic variation, diagnostic and surgical approach, and surgical outcomes in these patients. Results: The most common anatomic pattern was "3 by 1" (79%) followed by "2 by 2" (21%). The correct diagnosis by transthoracic echocardiography was made in 10 (71%) of the 14 patients. In contrast, preoperative computed tomographic (CT) angiography was performed in 10 patients and correct diagnosis was obtained in 8 (80%) of them. Pulmonary venous obstruction was seen in one patient before surgery. The in‐hospital mortality was 14% (2/14). Four patients had pulmonary hypertensive crisis in the postoperative period. The average follow‐up was 54 ± 27 months (range: 17–98 months) after surgical repair, and all surviving patients were asymptomatic. There was no late death. No clinically apparent sequelae were seen in six patients in whom isolated left superior pulmonary vein drainage was left uncorrected. Conclusion: An accurate diagnosis of anatomic pattern in mixed type TAPVC can be difficult to establish in all the patients before surgery. Detailed intraoperative assessment, individualized surgical approach, and aggressive perioperative management may reduce surgical mortality. Operative survivors have good midterm outcome.